SUMBER DAN INSPIRASI BELAJAR DALAM PENGEMBANGAN PENDIDIKAN KARAKTER ANAK USIA DINI - Utami Dewi, Ida Ayu Putu; Suyanta, I Wayan (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
AbstractHave we become inspirational teachers? Why should be an inspirational teacher? Have our students answered ?Master is inspiration? when someone asks ?children, what do you think about your teacher?? Good teachers who inspire teachers for learners, for example, advice, build learners to learn fun not stress and children are not afraid. Professional teachers should be able to educate children to be brave. Learning resources, all sources either in the form of data, people and certain forms that can be driven learners. Inspiration is interpreted with creative ideas that arise from within the self after an external stimulus. Therefore, teachers should be able to become ?stimulants? for their students, inspiring for inspiration so that children can always be encouraged to bring up ideas, ideas, thoughts, actions, values, and positive creativity. Learning is the most priority activity in school activities. In the learning activities, the teacher is like a captain who controls the pace of the learning process in the classroom. In this learning process, teachers are required to be able to plan, design and implement approach / learning model using the method until the proper learnin media. The principles of APE are principles of productivity, creativity, activity, effective and efficient, and interesting and fun. From a material perspective, APE must be able to develop thinking power (cognition), rapid power, language, motor and skill aspects. Through tools used as a means of play, so that the child is expected to develop the function of intelligence, emotion and spiritual so that emerging intelligence that skyrocketed.Keywords: My Teacher Inspiration, My Student SourceAbstrakSudahkah kita menjadi guru inspiratif? Mengapa harus menjadi guru inspiratif? Sudahkah siswa kita akan menjawab ?Guru adalah inspirasi? ketika ada orang yang bertanya tentang ?Nak, bagaimana pendapatmu tentang gurumu??Guru yang baik guru yang menginspirasi untuk peserta didik, sebagai teladan, contoh, nasehat membangun peserta didik agar belajar menyenangkan tidak tertekan dan anak tidak takut. Guru profesional harus dapat mendidik anak menjadi berani. Sumber belajar, semua sumber baik berupa data, orang dan wujud tertentu yang dapat digerak peserta didik. Inspirasi dimaknai dengan gagasan-gagasan kreatif yang muncul dari dalam diri setelah ada rangsangan dari luar. Maka dari itu, guru harus bisa menjadi ?perangsang? bagi siswanya, memberi inspirasi demi inspirasi agar anak senantiasa dapat terdorong untuk memunculkan ide, gagasan, pemikiran, tindakan, nilai, hingga kretifitas yang positif. Belajar merupakan kegiatan paling prioritas dalam aktifitas di sekolah. Dalam kegiatan pembelajaran, guru bagaikan nahkoda yang mengontrol laju proses pembelajaran di kelas. Dalam proses pembelajaran ini, guru dituntut untuk bisa merencanakan, merancang hingga melaksanakan pendekatan/model pembelajaran menggunakan metode hingga media pembelajaran yang tepat.